Building An Extranet: Connect Your Intranet With Vendors And Customers - Julie Bort; Bradley Felix (USA Wiley Computer Pub., 1997)
Expand your intranet to communicate directly and securely with your customers and suppliers Want to set up a Web page to automatically obtain bids from suppliers . . . invoice customers . . . conduct secure electronic transactions? . . . Find out how in Building an Extranet. The next wave in enterprise networking, extranets offer companies an exciting new way to leverage their investments in intranet technology. Functioning like private networks within the Internet, extranets enable companies to share information and selected applications with customers and suppliers and to conduct electronic commerce transactions --safely, securely, and inexpensively. The first complete, practical guide to understanding, building, and administering extranets, Building an Extranet arms you with all the background information, practical guidance, and source code you need to: Decide if an extranet is right for your company Calculate the costs and ROI of investing in the technology Determine which tools you'll need to create an extranet Create an extranet tailored to your company's needs Build applications that let customers check on or create an order, allow suppliers to create bids, and more
Keywords: Business enterprises; Computer networks; Intranets